THE INCREASE IN BODY WEIGHT, SMALL INTESTINE LENGTH, AND FEED CONVERSION RATIO (FCR) OF BROILER CHICKENS GIVEN HEAT STRESS AND BANANA BLOSSOM PEEL EXTRACT (Musa paradisiaca) - Agustina, Agustina; We Tenri Gading, Besse Mahbuba; Sukoco, Hendro; Cahyani, Annisa Putri; Pranatasari, Dewi (Jurnal Kedokteran Hewan, 2024)
This study aims to determine the increased of body weight, small intestine length, and food conversion ratio (FCR) of broiler chickens given heat stress and banana blossom peel extract (Musa paradisiaca). This study was an experimental study using a completely randomized design (CRD) consisting of five treatments. The experimental animals used in this study were female broiler chickens of the Cobb strain, 2 weeks old and weighing between 350-400 g, totaling 25 chickens. Chickens in P0 were not exposed to heat stress and banana blossom peel extract, while the chicken in P1, P2, P3, and P4 were exposed to heat stress and administered with 0.0, 500, 1000, 1500 mg/L banana blossom peel extract, respectively. The temperature in the heated cage accumulated slowly starting at 10:00 WIB and was maintained stable at 331 C for five hours. Banana blossom peel extract was given by dissolving it in drinking water for two hours (at 10:00) before the temperature in the cage reached 331 C. The data obtained were processed using the Kruskal-Wallis and continued with the Mann-Whitney Test. The results showed that there was a significant difference between treatments P1 and P4 on body weight gain and small intestine length (P0.05). Meanwhile, for the FCR value, only the P4 group met the standard, which was 1.57. Giving banana blossom peel extract at a dose of 1500 mg/L has been able to increase body weight, small intestine length, and decrease the FCR value in broiler chickens experiencing heat stress with a temperatu re of 331 C for 5 hours with a duration of 20 days.